2021
DOI: 10.1002/jso.26479
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted laparoscopic tumor enucleation is a feasible technique for renal hilar tumors: A retrospective study

Abstract: Background and Objective This study aimed to evaluate the safety and efficacy of robot‐assisted laparoscopic tumor enucleation (RAE) for the treatment of renal hilar tumors and to describe our experience with renorrhaphy‐related surgical techniques. Methods Retrospective data were collected from 173 consecutive patients who underwent RAE for localized renal tumors (cT1–cT2N0M0) at our hospital between September 2014 and November 2019. Results Seventy‐five patients had renal hilar tumors and 98 patients had non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, our subgroup analysis also demonstrated that the three subgroups had no statistically significant differences in PSM compared to the non-complex tumor group (p = 0.35; p = 0.18; p = 0.76) ( Figure 8 ). Similarly, no statistically significant difference in recurrence was found between the two groups (11 studies; p = 0.43) ( Figure 9 ) ( 17 , 18 , 20 , 21 , 23 30 ), and the subgroup analysis also illustrated no significant difference between the three subgroups and the non-complex group (p = 0.28; p = 0.16; p = 0.23). In terms of trifecta achievement, the pooled results revealed no difference between the two groups (seven studies; p = 0.05) ( Figure 9 ) ( 17 , 22 25 , 27 , 28 ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, our subgroup analysis also demonstrated that the three subgroups had no statistically significant differences in PSM compared to the non-complex tumor group (p = 0.35; p = 0.18; p = 0.76) ( Figure 8 ). Similarly, no statistically significant difference in recurrence was found between the two groups (11 studies; p = 0.43) ( Figure 9 ) ( 17 , 18 , 20 , 21 , 23 30 ), and the subgroup analysis also illustrated no significant difference between the three subgroups and the non-complex group (p = 0.28; p = 0.16; p = 0.23). In terms of trifecta achievement, the pooled results revealed no difference between the two groups (seven studies; p = 0.05) ( Figure 9 ) ( 17 , 22 25 , 27 , 28 ).…”
Section: Resultsmentioning
confidence: 80%
“…No statistically significant difference in intraoperative complications was observed between the two groups (seven studies; p = 0.49) (Figure S4) (23-25, 27-30). However, the complex group had more major complications compared to the non-complex group (12 studies; OR 2.35, 95% CI 1.50 to 3.67, p = 0.0002) (18)(19)(20)(22)(23)(24)(25)(26)(27)(28)(29)(30), while the subgroup analysis revealed that no significant difference in major complications between renal hilar and nonhilar tumors (p = 0.18) (Figure 5). Overall complications occurred in 27.9% (207 of 743 cases) of patients in the complex group and 20.0% (480 of 2439 cases) of patients in the non-complex group.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-year CSS was 90.8% in the training cohort and 81% in the validation cohort (P > 0.05). The characteristics of these patients are shown in Table 1 and Fig 2 [ 27 29 ].…”
Section: Resultsmentioning
confidence: 99%